A retextualização na construção do discurso jurídico acadêmico - Santos, ângela Maria Torres (2006)
This work analyses how the retextualization was used in juridical discourses by Law students in their Monographs. The concept of retextualization, including comprehension, was adaptated to observe the use of paraphrase in this context. We observed how the students see themselves as an author of their discourses, even when they do a simple copy of the ideas derived from other discourses. In addition, it was observed that the retextualization done by the students in their juridical discourses follow some linguistical strategies. The results pointed to a necessary reflection of the ways in which the juridical language has being taught in Law courses. Activities that make the students think more critically about their juridical discourse are necessary